PERAN PEMERINTAH MELALUI PROGRAM PELATIHAN DAN JOB FAIR DALAM MENGURANGI JUMLAH PENGANGGURAN MENURUT PERSPEKTIF EKONOMI ISLAM (STUDI PADA DINAS KETENAGAKERJAAN KABUPATEN ASAHAN) - Suci Ramadhani Siregar; Zuhrinal M. Nawawi; Mawaddah Irham (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
The role of the government through training activities and job fairs to reduce unemployment in Asahan Regency is seen from 3 indicators from the vision of the Asahan Regency Manpower Office, namely creating a competitive, productive, and prosperous workforce. This study aims to determine how the government's role in training programs and job fairs and the results of the analysis of the government's role in training and job fairs to reduce the number of unemployed according to the perspective of Islamic economics. The research methodology used is a qualitative research. Data collection techniques using interviews and documentation. The results of this study can be concluded that the government's role in reducing unemployment through training programs and job fairs is seen from the 3 indicators from the vision of the Asahan District Manpower Office that has played an optimal role and the results of the analysis of the government's role in training and job fairs to reduce the number of unemployed workers have not been able to reduce unemployment. The number of unemployment rates in Asahan Regency is still increasing every year, when viewed from the basic values ​​of Islamic Economics, the government's role in conducting training programs and job fairs to reduce the unemployment rate is fair and responsible, but the social security provided by the government can be said to be lacking effective because there are still many people who have not got a job after participating in the job fair.